2000
DOI: 10.1080/026870300401522
|View full text |Cite
|
Sign up to set email alerts
|

Boston Naming Test results for healthy older Australians: A longitudinal and cross-sectional study

Abstract: This study reports on a sample of normal Australian elderly who were assessed for naming ability using the Boston Naming Test (BNT). The study aimed to examine and compare the changes in naming ability, using both longitudinal and cross-sectional analysis, and determine the relationships between naming ability and age, educational level, visual acuity and gender and cultural relevance. Contradictory ®ndings were produced regarding age and were dependent on the research design. Longitudinal analysis showed no a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
24
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 27 publications
6
24
0
2
Order By: Relevance
“…She suggested that such a difference was caused by the considerably lower percentage of correct answers on some less universal items such as "pretzel", "beaver", and "asparagus". Cruice, Worrall, and Hickson (2000) obtained similar results in Australia. They recommended the substitution of "beaver" and "pretzel" by "platypus" and "pizza" when the BNT was to be applied in Australian samples.…”
Section: Introductionsupporting
confidence: 90%
“…She suggested that such a difference was caused by the considerably lower percentage of correct answers on some less universal items such as "pretzel", "beaver", and "asparagus". Cruice, Worrall, and Hickson (2000) obtained similar results in Australia. They recommended the substitution of "beaver" and "pretzel" by "platypus" and "pizza" when the BNT was to be applied in Australian samples.…”
Section: Introductionsupporting
confidence: 90%
“…Barker-Collo (2001) found that a sample of New Zealand university students scored significantly lower on the BNT than a sample from U.S. university students. Similar results were found in Australia by Cruice, Worrall, and Hickson (2000).…”
supporting
confidence: 93%
“…Similar to the findings of other studies (e.g. Belke & Meyer, 2007;Cruice et al, 2000;Figueredo Balthazar et al, 2008) age was also found to be negatively correlated with naming score. However, age and education may not be independent of each other in cross-sectional studies.…”
Section: Effects Of Age and Educationsupporting
confidence: 82%
“…languages on the test (e.g. Chinese (Cheung, Cheung, & Chan, 2004), Australian (Cruice, Worrall, & Hickson, 2000), Dutch-speaking Belgian (Mariën, Mampaey, Vervaet, Saerens, & De Deyn, 1998), Brazilian Portuguese (Miotto, Sato, Lucia, Camargo, & Scaff, 2010), Greek (Patricacou et al, 2007), Spanish (Peña-Casanova et al, 2009), French-speaking Quebec adults (Roberts & Doucet, 2011), and Swedish (Tallberg, 2005)). …”
Section: Introductionmentioning
confidence: 99%